PENGARUH WORK-LIFE BALANCE, WORK ETHICS, DAN WORK BEHAVIOR TERHADAP EMPLOYEE PERFORMANCE PADA DIVISI REGIONAL ACCESS MANAGEMENT TELKOM INDONESIA DIVISI REGIONAL 5 - Firmansyah, Ferdian Dwi; Tandiyono, Tan Evan (GEMAH RIPAH: Jurnal Bisnis, 2025)
This study aims to analyze the influence of Work-Life Balance, Work Ethics, and Work Behavior on Employee Performance in the Regional Access Management Division of Telkom Indonesia, Regional Division 5. In the context of human resource management, Employee Performance is an important aspect that is influenced by various behavioral factors and the work environment. This study uses a descriptive quantitative approach with a survey method, where data were collected through questionnaires from 55 respondents using census techniques. Data analysis was carried out using multiple linear regression using SPSS version 30. The results showed that Work Ethics and Work Behavior had a positive and significant effect on Employee Performance. This shows that high Work Ethics and good Work Behavior can significantly improve Employee Performance. Conversely, the Work-Life Balance variable showed a negative and significant effect on Employee Performance. This finding indicates that in the context of this study, the higher the employee's perception of work-life balance, the more likely it is to decrease work productivity, possibly because this perception has the potential to reduce focus on work.